New data on the genus Micromus Rambur, 1842 from China (Neuroptera, Hemerobiidae), with a key to Chinese species - Zhao, Yang; Tian, Yanlin; Liu, Zhiqi (Zootaxa, 2014)
A review of the genus Micromus Rambur from China is presented. A new species, Micromus setulosus sp. nov., which was found in Ningxia province, is described. The male of Micromus pallidius (Yang, 1987) and the female of Micromus perelegans Tjeder, 1936 are described for the first time in China. Keys to the adult males and females of the Micromus from China are also given.